A rare cause of recurrent acute pancreatitis. Issue 5 (13th July 2020) - Sonika, Ujjwal; Dalal, Ashok; Kumar, Ajay
Abstract : Annular pancreas is a rare entity. It clinically presents with intestinal obstruction. We present a case of a young female with incomplete annular pancreas presented with recurrent acute pancreatitis.